Enhancement of the photoelectric performance in inverted bulk heterojunction solid solar cell with inorganic nanocrystals. (1st January 2017) - Luan, Weiling; Zhang, Chengxi; Luo, Lingli; Yuan, Binxia; Jin, Lin; Kim, Yong-Sang
Highlights: Solid solar cells based on FeS2 or PbS NCs showed power conversion efficiency (PCE) of 3.0% and 3.11%, respectively. The FeS2 NCs/polymer solar cells showed good time and thermal stability when exposed in air condition. Ternary solid solar cells based on PbS NCs exhibited a higher short circuit current density ( Jsc ). Abstract: Nanocrystal/polymer solid solar cells have the advantages of low-cost, simple process, and flexible manufacture. In this work, ternary solid solar cells based on FeS2 and PbS nanocrystals exhibited photovoltaic conversion efficiency of 3.0% and 3.1%, respectively. As a kind of semiconductor with optical absorption in the visible and near-infrared regions, FeS2 nanocrystals matched well with the solar radiation spectrum. Furthermore, PbS Nanocrystals could increase the number of electrons, due to its multiple exciton effect. Additionally, the FeS2 nanocrystals solar cells showed high stability, with 83.3% of its initial efficiency remained after 15 weeks of exposure in air, and kept good stable performance at 20–80 °C. The photovoltaic conversion efficiency fluctuation magnitudes were also found to be smaller than quantum-dot sensitized solar cell under the same conditions.